Novel non-targeted LC-HRMS approaches in veterinary drug residue analysis and environmental analysis - Liesenfeld, Sabrina; Justus Liebig University Giessen (My University, 2021)
Liquid chromatography coupled with high resolution mass spectrometry (LC-HRMS) enables the implementation of non-targeted screening analysis and complements standard triple−quadrupole mass spectrometry in veterinary drug residue control as well as in environmental analysis. In this thesis, a workflow for processing and evaluation of non-targeted LC-HRMS metabolomics data was established and applied in two different projects. The aim of the first practical application was to gain further information about the origin of antibiotic residues in non-compliant samples taken within the frame of official veterinary drug residue control. The feasibility of a non-targeted metabolomics approach based on LC-HRMS data (LC-Q-Orbitrap and LC-Q-TOF) to distinguish between porcine muscle tissue from infected animals and from healthy animals was demonstrated. The differences arise from various compounds associated with metabolic changes in infected animals. Two new biomarker candidates have been identified: tripeptide prolylphenylalanylglycine and a lysophosphatidylcholine derivative. A bivariate data analysis procedure was performed to evaluate whether the presence of antibiotic residues points to a therapeutic application or may be the result of a contamination during sampling and/or analysis. In the second practical application, the environmental release of altrenogest (ALT), a synthetic progestogen which is used in modern pig production for estrus synchronization, was investigated. For certain geographical areas it cannot be excluded that the zootechnical use of ALT in gilts may present a risk for fish and other aquatic organisms, since manure of ALT-treated gilts may be used as fertilizer for agricultural soils. A pilot study was conducted in which spot urine samples from ALT-treated and non-medicated gilts were collected and analyzed using targeted and non-targeted LC-HRMS. The targeted investigation showed that glucuronide conjugates of ALT and its photo-isomerization product are main urinary metabolites of ALT in gilts. The concentration of ALT glucuronides is comparable to worst case calculations used for laboratory scale sorption studies. These results underline the need to perform field studies to determine the environmental input of ALT considering regional hotspots, i.e., pig breeding facilities. The chemometric analysis of the non-targeted data revealed a clear difference between ALT-treated gilts and control animals. Furthermore, a hydroxylated ALT glucuronide was identified at substance class level. Additional biomarker annotation and pathway mapping revealed changes in the metabolism of ALT-treated animals, which can be explained by ALT’s hormonal action. Taken together, the results of this thesis illustrate the exceptional potential of non-targeted LC-HRMS analyses and metabolomics workflows.
Keywords: veterinary drug residues; non-targeted LC-HRMS; metabolomics; ddc:500; ddc:540